Defeasible logic versus Logic Programming without Negation as Failure - Antoniou, G.; Maher, M.J.; Billington, D. (The journal of logic programming, 2000)
Recently there has been increased interest in logic programming-based default reasoning approaches which are not using negation-as-failure in their object language. Instead, default reasoning is modelled by rules and a priority relation among them. In this paper we compare the expressive power of two approaches in this family of logics: Defeasible Logic, and sceptical Logic Programming without Negation as Failure (LPwNF). Our results show that the former has a strictly stronger expressive power. The difference is caused by the latter logic's failure to capture the idea of teams of rules supporting a specific conclusion.